2021
DOI: 10.21203/rs.3.rs-257949/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Somatic whole genome dynamics of precancer in Barrett’s Esophagus

Abstract: While the genomes of normal tissues undergo dynamic changes over time, little is understood about the temporal-spatial dynamics of genomes in premalignant tissues that progress to cancer compared to those that remain cancer-free. Here we use whole genome sequencing to contrast genomic alterations in 427 longitudinal samples from 40 patients with stable Barrett’s esophagus compared to 40 Barrett’s patients who progressed to esophageal adenocarcinoma (ESAD). We show the same somatic mutational processes were act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
2
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 80 publications
(165 reference statements)
2
11
0
Order By: Relevance
“…Prior loss of TP53 enables genomic instability 7,8,24,25 , and we found a strong association in both FHCC and Cambridge cohorts between TP53 disruption (Supplementary Appendix) and ecDNA-positive status (Supplemental Figure 6a-b). In the FHCC cohort, all eight samples in which ecDNA was found prior to cancer diagnosis (TP-1) showed biallelic disruption of TP53 .…”
Section: Resultsmentioning
confidence: 61%
See 1 more Smart Citation
“…Prior loss of TP53 enables genomic instability 7,8,24,25 , and we found a strong association in both FHCC and Cambridge cohorts between TP53 disruption (Supplementary Appendix) and ecDNA-positive status (Supplemental Figure 6a-b). In the FHCC cohort, all eight samples in which ecDNA was found prior to cancer diagnosis (TP-1) showed biallelic disruption of TP53 .…”
Section: Resultsmentioning
confidence: 61%
“…We analyzed WGS data from esophageal biopsies in an independent, prospectively collected case-control study conducted at the Fred Hutchinson Cancer Center (FHCC) of patients with BE (Figure 1b.) 8 , including 40 patients with a cancer outcome (CO) and 40 patients who did not develop cancer (NCO) during the study period. At least two biopsies for WGS were obtained by isolating epithelial tissue (Figure 1c) of the BE at each of the two primary study time points - timepoint 1 (TP-1) and timepoint 2 (TP-2).…”
Section: Methodsmentioning
confidence: 99%
“…In multiple myeloma, Oben et al [165] showed that the presence of myeloma‐defining genomic events, including chromothripsis in the rarely progressing precursor state, monoclonal gammopathy of undetermined significance (MGUS), can define a more progressive subset. In oesophageal cancer, complex SVs and CNAs are the most accurate predictors of malignant transformation from the Barrett's oesophagus state [166–168].…”
Section: The Emerging Clinical Applications Of Svs In Cancermentioning
confidence: 99%
“…In the last decade, many studies have demonstrated proof-ofconcept data highlighting the potential that SVs can play in every stage of cancer, from screening to treatment to prognostication (Figure 3). Premalignancy, driver SVs can exist decades before the onset of symptoms, generating opportunities for screening and early detection [160,[164][165][166][167][168]. The TRACERx group [160] showed that chromosome 3p loss is often the initiating driver in clear cell renal cell carcinoma and is predicted to arise 30-50 years before diagnosis (Figure 3A).…”
Section: The Emerging Clinical Applications Of Svs In Cancermentioning
confidence: 99%
See 1 more Smart Citation